Marshall's syndrome - Neha Meena; Prafulla K Sharma; Minakshi Bhardwaj; Sawan Kumar (Wolters Kluwer Medknow Publications, 2016)
Marshall's syndrome is a form of acquired cutis laxa without systemic involvement. It is characterized by acute onset of multiple erythematous papule and plaques that resolve with postinflammatory elastolysis and cutis laxa. We report a case of 4-year-old boy with the typical features of Marshall's syndrome.